ANALISIS PENGARUH BAHAN BAKU, MODAL DAN TENAGA KERJA TERHADAP PRODUKSI BATU NISAN DI KECAMATAN MARITENGNGAE KABUPATEN SIDENRENG RAPPANG - Akhsan, Akhsan; Ladung, Fajar; Nurfazila, Nurfazila (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2021)
The industrial sector makes a very important contribution to employment. The increasing number of residents will at the same time increase the number of workers in industrial areas to encourage the creation of various economic activities to meet the needs of life. The purpose of this study was to analyze and determine the factors that influence the production of tombstones in the Maritengngae District, Sidenreng Regency Rappang. The variables observed in this study were the production of tombstones (Y), raw materials (X1), capital (X2), and labor (X3). The type of research used is quantitative research. Where the data used in the form of primary data was obtained through questionnaires and analyzed by multiple linear regression analysis techniques with SPSS version 24 application program to analyze the effect of tombstone production in Sidenreng Rappang District, Maritengngae District. The results of this study found that the variables of raw materials, capital, and labor had a significant effect on the tombstone production variable.